2020
DOI: 10.1021/acsomega.9b03067
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Crystallization of Sodium Dodecyl Sulfate·1/8 Hydrate by Evaporation, Antisolvent Addition, and Cooling

Abstract: Sodium dodecyl sulfate (SDS)·1/8 hydrate (NaC12H25SO4·1/8H2O) crystals were successfully produced by evaporation, antisolvent addition, cooling crystallization, and isothermal aging in a common stirred tank. A clear 33.3 wt % SDS aqueous solution was concentrated by evaporation to a 60 wt % coagel consisting of numerous SDS hydrates and water. The coagel was transformed to a clear solution when two times the volume of acetone relative to the water remaining were added. By this fluid property, a controlled crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Those hydrate forms, excluding SDS·1/8 hydrate, were prepared and formed in purely aqueous media. It was reported that its 1/8 hydrate is stable under normal conditions. , In addition, one crystal structure of the anhydrous SDS form has already been determined using a combination of synchrotron radiation powder diffraction and molecular modeling, while SDS is apt to absorb and bind to water molecules in air at ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Those hydrate forms, excluding SDS·1/8 hydrate, were prepared and formed in purely aqueous media. It was reported that its 1/8 hydrate is stable under normal conditions. , In addition, one crystal structure of the anhydrous SDS form has already been determined using a combination of synchrotron radiation powder diffraction and molecular modeling, while SDS is apt to absorb and bind to water molecules in air at ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Oftentimes, a short evaporation time like this makes it difficult to have a good control over the crystalline form of its product to be specific. SDS is highly soluble in water and forms micelles in aqueous solution above 8.2 mM, which is its CMC at 25 °C. , As the solute concentration of SDS in aqueous solution increases by reducing its water content, the SDS solution will pass through several complex phases of micelles, liquid crystals, and coagels toward the formation of a very thick slurry, causing poor mixing, and heat and mass transfer . The strong affinity to water of those structures often makes the removal of water from the slurry with high viscosity very difficult and energy-consuming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its wide range of applications, the phase behavior of aqueous solutions of SDS and its hydrated crystals, at equilibrium and in static conditions, has been extensively investigated over the past decades. ,, Nevertheless, the kinetics of phase transformations upon variations of temperature and concentration and those occurring in the vicinity of the interfaces remain largely unresolved. Here, we focus on transformations from the micellar L 1 to the crystalline C phase that occur upon cooling at fixed surfactant concentration.…”
Section: Resultsmentioning
confidence: 99%